Pengaruh Struktur Kepemilikan, Pertumbuhan Aktiva, Profitabilitas, Ukuran Perusahaan, Risiko Bisnis dan Struktur Aktiva terhadap Struktur Modal pada Perusahaan yang Listed di BEI dalam Kategori LQ45 - Purwaningsih, -; Wibisono, Haris; Rustiyaningsih, Sri (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
The aim of this research is to prove that the structure of ownership, the growth of assets, the profitability, the standard of company, the risk of business, and also the structure of assets are influential empirically. In this case, all these matters influence the capital structure of company which is listed in BEI (Indonesia Economic Bank), category of LQ45 during 2010 – 2014. Further, the technique of sample collecting that is used in this research is purposive sampling method. There are 17 companies which are chosen as sample. Moreover, the test of hypothesis applies multiple linier regression analysis. The result of this analysis with the SPSS 17.0 program assistance indicates that the structure of ownership variable, the standard of company, the risk of business, and the structure of assets influence the capital structure of company. Meanwhile, the growth of assets and profitability do not influence the capital structure of company.